2019
DOI: 10.1002/elan.201800719
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive & Long‐lasting Neural Probes from a Materials Perspective

Abstract: Neurological disorders in aging society have created the need to understand how the brain works. At present, there are limited engineered “non‐invasive” tools to study and characterize the brain activity. Advancement in neuroscience research is highly focused on the fabrication of implantable neural probes that can effectively integrate with the neural tissue. Challenges associated with the commercially available probes has driven the development of mechanically compliant and non‐invasive neural implants. Engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Nevertheless, traditional electrode materials have high rigidity relative to the human skull. This mismatch in mechanical properties can result in brain damage [142], which limits the application of this technology for clinical diagnosis and treatment.…”
Section: Microelectrode Array Eitmentioning
confidence: 99%
“…Nevertheless, traditional electrode materials have high rigidity relative to the human skull. This mismatch in mechanical properties can result in brain damage [142], which limits the application of this technology for clinical diagnosis and treatment.…”
Section: Microelectrode Array Eitmentioning
confidence: 99%
“…One of the significant advantages of CNT electrodes is their electrical and mechanical interface with neurons. Their tridimensional structure and high surface area increases electrode capacitance, lowers the impedance, therefore enabling size reduction of the electrodes to achieve high density devices with high efficacy local stimulation, and reduces the tissue inflammatory response (240,242,(251)(252)(253). Vitale et al demonstrated neural recording and stimulation using CNT fiber electrodes, when neurons in vivo were activated as efficiently as metal electrodes with a 10 times larger surface area (254).…”
Section: Cntsmentioning
confidence: 99%
“…Nano electrodes with increased roughness, using nanowires, graphene, conductive polymers or carbon nanotube (CNT) coatings can resolve long-standing challenges ( 95 , 216 , 240 ). In particular, carbon nanotubes ( 241 , 242 ) which exhibit Young's Modulus as high as 1 TPa and tensile strength of 100 GPa, can bend and twist without breaking, and are therefore an appealing material for stable, thin and flexible electrodes ( 243 245 ). CNTs are known for their utility in recording neuronal signaling, demonstrating reduced impedance and much higher signal to noise ratio ( 156 , 217 , 246 248 ).…”
Section: Electrode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, new membrane materials that are compatible with microfabrication techniques could allow for adaptation of recently reported material/device architectures that mitigate the foreign body response. This is particularly important as the foreign body response is well-known to limit the long-term efficacy of medical implants for drug delivery and sensing. …”
mentioning
confidence: 99%